Analisis Respon Pemakai Jasa Transportasi Taksi Konvensional Terhadap Keberadaan Taksi Online di Pontianak - andry lindi lim (President University, 2020)
Analysis of the Response of Conventional Taxi Transportation Service Users to the Existence of Online Taxis in Pontianak is a problem raised in this study, and the authors limit it to: Qualitative and Quantitative Analysis and Measures of Availability of Analysis of Public Facilities. Descriptive methods and data collection techniques are done by conducting interviews, documentary studies and questionnaires. The population is Conventional Taxi Service Users and Online Taxis in Pontianak. The sampling technique from the population used purposive sampling with 100 respondents. The results showed that Transportation Minister Decree Variable Number 26 Year 2017 Article 5 Regarding Transportation Services of People Using Conventional and Online Taxis has an overall average of 6.00 and 7.67, and Variable Size of Decision to Use Taxis has an overall average of 6.25 and 7.50. Key words: Analysis of the taxi passengers